Fanzine: procedimentos construtivos em mídia tática impressa - Lourenço, Denise (2007)
This work is a reflection on creation procedures of fanzines, low cost production magazines that propagate comics, poems, drawings, texts and glues produced for this specific end or loaned of other daily situations to belong to the fanzine universe. First we point out the object of Fanzine studies in Brazil in the field of the production diversity, impression and distribution. After that we present the analysis of creation specificities, in the chapter on constructive procedures. We arrive at the third chapter when we discourse on Tactical Media, a provisory concept that escapes of the literal translation of the word fanzine (fanaticmagazine or fan magazine) and of the setting of these magazines in the prejudiced and vague definition of the term reviewed alternative . We lock up locating some public spaces that conserve fanzines collections and pointing fanzines workshops experiences as media laboratories and not as only playful pastime to cut and glue